Red and blue nation? characteristics and causes of America's polarized politics. Vol. 1 - Nivola, Pietro S.; Brady, David W. (Hoover Institution on War, Revolution, and Peace, Stanford University ; Brookings Institution Press, 2006)
"Considers the extent to which polarized views among political leaders and activists are reflected in the population at large. Pays particular attention to factors such as the increased influence of religion and the changing nature of the media and offers thoughtful analyses of the underlying problems"--Provided by publisher.